2017
DOI: 10.1016/j.apjtm.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of taurine on immune function in mice with T-cell lymphoma during chemotherapy

Abstract: Taurine can effectively enhance the immune function of mice with T-cell lymphoma during chemotherapy, reduce the toxicity of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…By contrast, significant differences were observed in hydrolytic GABA, taurine (TAU), α ‐aminobutyric acid, ANS, ethanolamine (ETN), and 1‐MHIS content, with TAU and ETN content about fourfold higher in bovine colostrum than in human colostrum. Previous studies reported TAU involvement in important biological functions, such as osmoregulation, membrane stabilization, digestion, and the endocrine and immune systems . Analysis of the total amount of hydrolytic amino acids revealed levels of 4.2 g L −1 and 2.2 g L −1 in bovine and human colostrum respectively.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…By contrast, significant differences were observed in hydrolytic GABA, taurine (TAU), α ‐aminobutyric acid, ANS, ethanolamine (ETN), and 1‐MHIS content, with TAU and ETN content about fourfold higher in bovine colostrum than in human colostrum. Previous studies reported TAU involvement in important biological functions, such as osmoregulation, membrane stabilization, digestion, and the endocrine and immune systems . Analysis of the total amount of hydrolytic amino acids revealed levels of 4.2 g L −1 and 2.2 g L −1 in bovine and human colostrum respectively.…”
Section: Resultsmentioning
confidence: 90%
“…Previous studies reported TAU involvement in important biological functions, such as osmoregulation, membrane stabilization, 45 digestion, and the endocrine and immune systems. 46 Analysis of the total amount of hydrolytic amino acids revealed levels of 4.2 g L −1 and 2.2 g L −1 in bovine and human colostrum respectively.…”
Section: Comparison Of 22 Non-proteinogenic Amino Acids In Bovine Andmentioning
confidence: 97%
“…The thymus and spleen indexes may be used to directly reflect the level of immune function in humans. When ascites tumors form in mice, abnormalities in immune organ function is indicated by a decrease in spleen and thymus indexes ( 28 ). In the present study, the thymus index in the Dox group was decreased compared with healthy control group, indicating that the immune function of mice was suppressed and may have been the cause of the reduced survival in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the beneficial action of taurine has been proved to be helpful in attenuating the side effects of chemotherapy, thus potentiating the immune function of mouse T-cell lymphoma. After quantification of pro-inflammatory mediators IL-4, IL-12 and IFN-γ, it was observed that there was a greater decline in the taurine/chemotherapy-treated group of mice compared to the chemotherapy group (186). In addition, taurine emerged as the promising agent that bypassed the toxic injuries derived from the combination of gemcitabine and cisplatin, thereby maximizing the efficacy of chemotherapeutic drugs (187).…”
Section: Beneficial Effect Of Taurine In Various Cancers (In Vitro Anmentioning
confidence: 99%
“…The therapeutic efficacy of taurine was presented very strongly against peripheral T-cell lymphoma, given that the tumor inhibition rate was remarkably higher in the group treated with chemotherapy drugs and taurine compared to chemotherapy group alone (187). Taurine exerted its ameliorative action, by normalizing Th1/Th2 cytokine levels in both spleen and thymus (186).…”
Section: Beneficial Effect Of Taurine In Various Cancers (In Vitro Anmentioning
confidence: 99%